Uji Efektivitas Trichoderma asperellum dalam Pengendalian Nematoda Puru Akar (Meloidogyne spp.) Secara In Vitro - Sisi Indriyani; I Gede Swibawa; Ni Kadek Emi Sintha Dewi; Cipta Ginting (Jurnal Proteksi Agrikultura, 2026)
Root-knot nematodes (Meloidogyne spp.) are significant pests that damage the root systems of plants and are difficult to control using conventional methods. The use of chemical nematicides carries the risk of environmental contamination, so environmentally friendly control alternatives are needed, one of which is using the biological agent Trichoderma asperellum. This study aims to determine the effect of spore concentration and exposure duration of T. asperellum on the hatching of Meloidogyne spp. eggs in vitro. The research was conducted at the Plant Pest Science Laboratory and the Biotechnology Laboratory of the Faculty of Agriculture, University of Lampung, from May to July 2025. The experiment used a completely randomized design (CRD). The first experiment tested five concentrations of spore suspension dilutions (10-1, 10-2, 10-3, 10-5, and a control), while the second experiment tested exposure durations of 10, 15, 30, and 60 minutes. The results showed that a concentration of 10-2 (2.7 × 105 spores/mL) was able to inhibit egg hatching by 50.90%, which was higher than the other concentrations. In the duration test, juvenile mortality increased over time, reaching 85.37% at 10 minutes and 99.83% at 60 minutes. In conclusion, a 10-2 concentration with a minimum exposure of 30–60 minutes is effective in reducing the hatching rate of Meloidogyne spp. eggs and has the potential to be applied as an environmentally friendly biological control.